Percepatan Inklusi Keuangan untuk Meningkatkan Pertumbuhan Ekonomi, Lebih Terinklusif, dan Merata Di Era Presidensi G20 - Sriary Bhegawati, Desak Ayu; Novarini, Ni Nyoman Ari (Jurnal Akuntansi, Manajemen, Bisnis dan Teknologi, 2023)
Indonesia in increasing financial inclusion in recent years has been supported by a strong commitment from the government and the private sector, as well as rapid technological innovation, especially those that support the provision of digital financial services or digital financial services (DFS). This study aims to determine if technological innovations in the financial sector can help accelerate financial inclusion. As well as the efforts/steps taken by the government to increase access to financial institutions, especially the lower middle class. The data analysis technique used in this research is descriptive qualitative analysis. Methods Data collection used a global literature study, data analysis, and interviews with stakeholders in the DFS sector. The results of this study state that the first is related to financial inclusion and MSME financing in a two-day meeting to discuss GPFI's commitment to continue to take advantage of opportunities in the digital era. Second, strengthening MSME financing guidelines. Third, the importance of increasing the role and potential of youth and women to achieve an inclusive economy, Fourth, the need for efforts to encourage the use of digitalization to achieve financial inclusion through the implementation of the G20 High Level Principles (HLPs) for Digital Financial Inclusion